Save the doctor and the nurse - Murtuza Ghiya (Research and Humanities in Medical Education, 2020)
COVID-19 has exposed the weakness in a largely privatized, profit driven health-care business, soaked neck deep in corruption both within and without the so called noble health care system. This is likely to have stemmed from years of under-funding of health care (% GDP spent on health care makes India rank one of the lowest in the world).